2017
DOI: 10.1002/jhbp.520
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic predictability of the new American Joint Committee on Cancer 8th staging system for distal bile duct cancer: limited usefulness compared with the 7th staging system

Abstract: The 8th AJCC staging for DBD cancer does not have better prognostic predictability than the 7th stage does. The previous pathologic results would become useless unless they were reviewed entirely. Therefore, introduction of the AJCC 8th staging has to be reconsidered, especially for new T staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…Firstly, in Kiriyama M et al's paper [14], patients with PLNs � 4 were only 10% (37/370), and the patients from Japan was selected, which may not be suitable for European and American countries. Secondly, two large sample studies found no difference in prognosis between patients with PLNs � 4 and 1-3 [10,24], which was consistent with the results of this study. Thirdly, we found that among patients with ELNs � 5, using the optimal cut-off value of PLNs (0, 2) could accurately stratify patients (Fig 2C), but the recommendation of the number of PLNs by the AJCC (0, 3) could not ( Fig 2D).…”
Section: Plos Onesupporting
confidence: 91%
“…Firstly, in Kiriyama M et al's paper [14], patients with PLNs � 4 were only 10% (37/370), and the patients from Japan was selected, which may not be suitable for European and American countries. Secondly, two large sample studies found no difference in prognosis between patients with PLNs � 4 and 1-3 [10,24], which was consistent with the results of this study. Thirdly, we found that among patients with ELNs � 5, using the optimal cut-off value of PLNs (0, 2) could accurately stratify patients (Fig 2C), but the recommendation of the number of PLNs by the AJCC (0, 3) could not ( Fig 2D).…”
Section: Plos Onesupporting
confidence: 91%
“…Including our present study, several previous studies demonstrated the prognostic significance of the 3 tiered N category [13,22,23,25]. In present study, we observed significant survival differences among DBDC patients based on N category of the eighth AJCC staging system in overall comparison and in pairwise comparison between N0 and N1 patients, similar to the previous studies [13,22,23,25].…”
Section: Discussionsupporting
confidence: 91%
“…A few previous studies validated T category of the eighth AJCC staging scheme of DBDCs [13,25]. Moon et al [13] demonstrated the superiority of the eighth edition to the seventh edition for predicting patient prognosis, similar to our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Two external validation studies failed to show significant survival discrimination among the proposed 8th T stage criteria [27,29], and one of these studies proposed different cutoff values for tumor invasion depth, based on T stage [29]. A previous study revealed that the new 8th AJCC T stage did not have better prognostic predictability than the 7th [30]. To validate the proposed 8th T stage, researchers need to review all histologic slides again, which is timeconsuming and impossible; and therefore, the introduction of the proposed 8th AJCC T stage should be reconsidered.…”
Section: Discussionmentioning
confidence: 99%